2010
DOI: 10.3139/217.2347
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Polymer Stretching Instabilities: Application to Film Blowing

Abstract: International audienceFilm blowing, as other elongational polymer forming processes, may present marked drawing instabilities leading to unacceptable products. But in film blowing, these instabilities are much more complex than for example in fibre spinning: there is no stabilizing effect of the polymer cooling, and the symmetry of the process may be broken, leading in some processing conditions to so called helical instabilities. Stability of the process has been investigated using a strategy inspired from sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…By comparing the bubble stability of different types of PE, Minoshima and White concluded that long‐chain branched PEs are the most stable. The most unstable are PEs with narrower molecular weight distributions (MWD) . However, there are no articles dedicated to the blown extrusion processing of PLA and the improvement of its stability window.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing the bubble stability of different types of PE, Minoshima and White concluded that long‐chain branched PEs are the most stable. The most unstable are PEs with narrower molecular weight distributions (MWD) . However, there are no articles dedicated to the blown extrusion processing of PLA and the improvement of its stability window.…”
Section: Introductionmentioning
confidence: 99%
“…The same type of phenomenon as in cast-film may be expected, that means a periodic fluctuation of thickness and diameter (figure 6) (Kanai and White, 1984;Minoshima and White, 1986;Ghaned-Fard et al, 1996;Laffargue et al, 2002Laffargue et al, , 2010. In fact a non-axisymmetric instability may also be observed, which corresponds to a helical shape of the bubble between the die exit and the film freezing line (figure 7).…”
Section: Methodsmentioning
confidence: 83%
“…On the contrary, for a Bur of 3.25, the bubble radius remains constant when increasing Dr from 6.6 to 7.1, but at the same time the centre of the bubble rotates (figure 9) in an horizontal plane giving a helical shape to the bubble. Laffargue et al (2010) performed film blowing experiments on various extrusion lines but with the same LLDPE. They point out the existence of a stability hill splitting stable and unstable blowing conditions (for both axisymmetric and helical instabilities (figure 10)).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Component σ n is small compared to σ t and σ φ . It can be proven, using an expansion according to the small parameter , that σ n is of order while σ t and σ φ are of order 1 (see [5] and [6]). Using σ n = 0 we have p = 2η V e de ds and using (3) we obtain finally:…”
Section: Behaviormentioning
confidence: 99%